Ecolinguística: um enquadramento conceitual - Bang, Jørgen Christian (2015)
Linguistics and applied linguistics have tried to show themselves as neutral, like natural sciences. Here, language and linguistics are evaluated as part of social activity constituting and being constituted by social praxis, inside a meaning process based on values. Social praxis is made up of various nuclear contradictions: culture-nature, private-public, city-country. Ecolinguistics is part of critical applied linguistics which focuses the ways language and linguistics are involved in the ecological crisis. It is a theory of language which is both partisan and objective. This dialectic model of language includes a semantic matrix, which explains the diverse types of meaning. It is a dialogic model which, as a matter of fact, is not ‘duologic’ as traditional models. It includes a third participant, i.e., S1, S2, S3. All this from the bio-logic, socio-logic, and ideo-logic dimension. Reference comprises the lexical, anaphoric and deictic dimension. Our ecologic and dialectic theory of language is a critique to the culture which produces the ecologic crisis and to its traditional theories of language. The essay ends by analyzing two legal texts about organic production.